Graphene Optoelectronics: Atomic‐Scale Spectroscopic Imaging of the Extreme‐UV Optical Response of B‐ and N‐Doped Graphene (Adv. Funct. Mater. 52/2019). (23rd December 2019) - Hage, Fredrik S.; Kapetanakis, Myron D.; Idrobo, Juan‐Carlos; Ramasse, Quentin M.; Kepaptsoglou, Demie
Abstract : In article number 1901819, Myron D. Kapetanakis, Quentin M. Ramasse, Demie Kepaptsoglou, and co‐workers use advanced electron energy loss spectroscopy to probe the plasmonic and optical response of nitrogen‐ and boron‐doped graphene at the atomic scale. Single atom dopants in graphene can be manipulated to engineer localised optoelectronic properties, which can be mapped experimentally and understood through theoretical calculations based on density functional theory.